Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/ncomms6280
|View full text |Cite
|
Sign up to set email alerts
|

Manganese hexacyanomanganate open framework as a high-capacity positive electrode material for sodium-ion batteries

Abstract: Potential applications of sodium-ion batteries in grid-scale energy storage, portable electronics and electric vehicles have revitalized research interest in these batteries. However, the performance of sodium-ion electrode materials has not been competitive with that of lithium-ion electrode materials. Here we present sodium manganese hexacyanomanganate (Na 2 Mn II [Mn II (CN) 6 ]), an open-framework crystal structure material, as a viable positive electrode for sodium-ion batteries. We demonstrate a high dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
315
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(324 citation statements)
references
References 35 publications
8
315
1
Order By: Relevance
“…In the HCF structure, the inserted cations could influence the C N bonding strain by the ionic radius difference between K + and Cs + [48]. Moreover, the XRD patterns ( 6 ] and concluded that the XRD patterns were ascribed to the appearance of new phases by adsorption of Cs + [49].…”
Section: Ion Exchange Of Kcuhcf With Cs +mentioning
confidence: 99%
“…In the HCF structure, the inserted cations could influence the C N bonding strain by the ionic radius difference between K + and Cs + [48]. Moreover, the XRD patterns ( 6 ] and concluded that the XRD patterns were ascribed to the appearance of new phases by adsorption of Cs + [49].…”
Section: Ion Exchange Of Kcuhcf With Cs +mentioning
confidence: 99%
“…Prussian blue analogues (PBA)—ATM[TM′(CN) 6 ] 1− x · y H 2 O (A = alkali; TM = transition metal)—have recently received attention as cathode materials for rechargeable non‐aqueous Li‐ion,20, 21, 22 Na‐ion,23, 24, 25, 26, 27, 28, 29 Ca‐ion,30 aqueous divalent‐ion,31 and Al‐ion batteries 32. In this structure, cyano (C≡N − ) ligands are highly covalently bonded to the transition metal ions (TM 2+/3+ ) owing to strong π‐backbonding, gaining much better chlorination resistance than oxo (O 2− ) ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Among nanoporous materials, transition metal hexacyanoferrates or Prussian blue and its analogues (PBAs), denoted as A x M[Fe(CN) 6 ] y (A and M, are the alkali and transition metals, respectively), are most intensively investigated for LIBs [2][3][4][5][6][7][8] and sodium-ion secondary batteries (SIBs) [9][10][11][12][13]. The PBAs consist of three-dimensional cyano-bridged networks (jungle-gym type networks) of the transition metal, -M-NC-Fe-CN-M-, with periodic nano-cubes of 5 Å on each side [14,15].…”
Section: Introductionmentioning
confidence: 99%